2021
DOI: 10.3233/ch-219202
|View full text |Cite
|
Sign up to set email alerts
|

Early evaluation of organ failure using MELD-XI in critically ill elderly COVID-19 patients

Abstract: PURPOSE Critically ill elderly patients who suffer from Sars-CoV-2 disease are at high risk for organ failure. The modified MELD-XI score has not been evaluated for outcome prediction in these most vulnerable patients. METHODS The Corona Virus disease (COVID19) in Very Elderly Intensive Care Patients study (COVIP, NCT04321265) prospectively recruited patients on intensive care units (ICU), who were = 70 years. Data were collected from March 2020 to February 2021. The MELD-XI score was calculated using the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…With the last reported LVEF and classification into HFrEF, HFmrEF, and HFpEF, the study captures other prognostically important parameters in CHF. Our study shares methodological limitations with the other COVIPstudies 3,7,22,[32][33][34] : our study lacks a control group of younger COVID-19 patients for comparison or a comparable age cohort of patients who were not or could not be admitted to the ICU. Furthermore, the COVIP database does not store information on pre-ICU care and triage.…”
Section: Limitationsmentioning
confidence: 99%
“…With the last reported LVEF and classification into HFrEF, HFmrEF, and HFpEF, the study captures other prognostically important parameters in CHF. Our study shares methodological limitations with the other COVIPstudies 3,7,22,[32][33][34] : our study lacks a control group of younger COVID-19 patients for comparison or a comparable age cohort of patients who were not or could not be admitted to the ICU. Furthermore, the COVIP database does not store information on pre-ICU care and triage.…”
Section: Limitationsmentioning
confidence: 99%
“…While our study was conducted, few studies were had already evaluated the relationship between in-hospital (short-term) mortality o, length of intensive care, length of hospital stay, and long-term mortality of COVID-19 and the MELD-XI score [26][27] . In one of these studies, a higher MELD-XI score was found to be associated with mortality in COVID-19 patients without liver disease, and it was stated that it could be a helpful tool for other risk modalities 26 .…”
Section: Discussionmentioning
confidence: 99%
“…In one of these studies, a higher MELD-XI score was found to be associated with mortality in COVID-19 patients without liver disease, and it was stated that it could be a helpful tool for other risk modalities 26 . In another study, it was shown that the MELD-XI score may be useful in predicting early mortality in the elderly and critically ill patients 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The present study has some methodological limitations in common with the other COVIPstudies [29][30][31][32][33], such as COVIP does not contain a control group of younger COVID-19…”
Section: Limitationsmentioning
confidence: 99%